KONTRIBUSI KERAJAAN ACEH TERHADAP PERKEMBANGAN LEMBAGA DAN SISTEM PENDIDIKAN ISLAM DI SUMATERA - Sri Wahyuni; Rezki Amelya; Idrus Latif (Najah Bestari, 2026)
This study examines the contribution of Kerajaan Aceh to the development of Islamic organizations and educational systems in Sumatera, with a historical focus on traditional dayah, mosque, and ulama organizations, as well as on curriculum elements, teaching methods, and the role of the sultan in education. This study used a kualitatif pustaka research methodology to examine articles and books related to Acehnese history, the structure of the Islamic education organization in Aceh, the mechanisms of knowledge acquisition, and the impact of kerajaan policies on the formalization of Islamic education. The thematic results indicate that Aceh's dayah, rangkang, meunasah, surau, and mosque institutions serve as places of education, moral culture, and dakwah that significantly contribute to the advancement of knowledge in the Nusantara region. The context of